(untitled) (Journal of Plant Disease Sciences, 2023)
A lab experiment was carried out in the Department of Plant Pathology, Rajasthan College of Agriculture, Udaipur (Rajasthan), to determine the additive effect of temperature and pH on Rhizoctonia solani isolates causative agent of Ajwain root rot collected from different locations. The results revealed that all eight isolates of R. solani showed the greatest mycelial growth at 30°C, the greatest sclerotial formation at 35°C, and the least at 15 °C. The pH relationship of R. solani mycelial growth and sclerotial formation was determined in vitro at different pH levels ranging from 4.0 to 8.0 at 20°C. R. solani grew at a wide range of pH levels, according to the current research. R. solani isolates showed the greatest growth and sclerotial formation at pH 7 and the least at pH 4.